Nitrogen release and synchrony in organic and conventional farming systems of the central highlands of Kenya - Musyoka, M.W.; Adamtey, N.; Bünemann, Else K.; Muriuki, A.W.; Karanja, E.N.; Mucheru-Muna, M.; Fiaboe, K.K.M.; Cadisch, Georg (Springer, 2019)
To match Nitrogen (N) supply to crop N demand, it is essential to understand N release and uptake patterns in different farming systems and crops. To assesses the dynamics of N released in organic and conventional systems and potential synchrony and asynchrony in crop N uptake, a study was conducted over three cropping seasons (potato, maize and leafy vegetables) at two sites in the Central Highlands of Kenya. Mineral-N release and synchrony were monitored in conventional and organic systems at high (recommended N, P, pesticides and irrigation) and low input (low N, P, pesticide use and rainfed) systems. Mineral-N release was assessed using in situ buried bags and N synchrony was measured by the daily differences in N fluxes. The percentage of N applied released during potato (38%) and vegetable (44%) cropping seasons were similar between systems. However, under maize strong temporal N immobilization from inputs occurred, particularly at Thika, related to the poor quality of manure and compost (lignin:N ratio > 13). In all systems, excess-asynchrony of available N was pronounced during vegetative stages and at harvest, while insufficient-asynchrony occurred at reproductive stages. During potato cropping season at Thika, Org-High showed highest positive N fluxes (> 20 kg N ha−1 day−1) at planting and tuber bulking stage. At early stages of maize and vegetables Org-Low and Org-High experienced up to 5 times larger negative N fluxes (insufficiency) compared to conventional treatments at Chuka site. The study recommends reducing N applications at planting and increasing N dosages at reproductive stages of crops.